Mucosal adjuvanticity of fibronectin-binding peptide (FBP) fused with Echinococcus multilocularis tetraspanin 3: systemic and local antibody responses. - Zhisheng Dang; Jinchao Feng; Kinpei Yagi; Chihiro Sugimoto; Wei Li; Yuzaburo Oku (Public Library of Science (PLoS), 2012)
BACKGROUND: Studies have shown that a bacterial fibronectin attachment protein (FAP) is able to stimulate strong systemic and mucosal antibody responses when it is used alone or co-administrated with other antigens (Ags). Thus, it has been suggested to be a promising adjuvant candidate for the development of efficient vaccines. However, the co-administered Ags and FAP were cloned, expressed and purified individually to date. In a recent study, we first evaluated the adjuvanticity of a fibronectin-binding peptide (FBP, 24 amino acids) of Mycobacterium avium FAP fused with Echinococcus multilocularis tetraspanin 3 (Em-TSP3) by detecting systemic and local antibody responses in intranasally (i.n.) immunized BALB/c mice. METHODOLOGY/PRINCIPAL FINDINGS: Em-TSP3 and FBP fragments were linked with a GSGGSG linker and expressed as a single fusion protein (Em-TSP3-FBP) using the pBAD/Thio-TOPO expression vector. BALB/c mice were immunized i.n. with recombinant Em-TSP3-FBP (rEm-TSP3-FBP) and rEm-TSP3+CpG and the systemic and local antibody responses were detected by ELISA. The results showed that both rEm-TSP3-FBP and rEm-TSP3+CpG evoked strong serum IgG (p<0.001) and IgG1 responses (p<0.001), whereas only the latter induced a high level IgG2α production (p<0.001), compared to that of rEm-TSP3 alone without any adjuvant. There were no significant differences in IgG and IgG1 production between the groups. Low level of serum IgA and IgM were detected in both groups. The tendency of Th1 and Th2 cell immune responses were assessed via detecting the IgG1/IgG2α ratio after the second and third immunizations. The results indicated that i.n. immunization with rEm-TSP3-FBP resulted in an increased IgG1/IgG2α ratio (a Th2 tendency), while rEm-TSP3+CpG caused a rapid Th1 response that later shifted to a Th2 response. Immunization with rEm-TSP3-FBP provoked significantly stronger IgA antibody responses in intestine (p<0.05), lung (p<0.001) and spleen (p<0.001) compared to those by rEm-TSP3+CpG. Significantly high level IgA antibodies were detected in nasal cavity (p<0.05) and liver (p<0.05) samples from both groups when compared to rEm-TSP3 alone without any adjuvant, with no significant difference between them. CONCLUSIONS: I.n. administration of rEm-TSP3-FBP can induce strong systemic and mucosal antibody responses in immunized BALB/c mice, suggesting that fusion of Em-TSP3 with FBP is a novel, prospective strategy for developing safe and efficient human mucosal vaccines against alveolar echinococcosis (AE).